REMEDIASI MISKONSEPSI SISWA PADA MATERI HUKUM I NEWTON MENGGUNAKAN MODEL PEMBELAJARAN TGT DI SMP - RUSVITA, ERLINA; Sahala Sitompul, Stepanus; Mursyid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
This study aims to find out the effectiveness of Teams Games Tournament (TGT) Model in remediating students’ misconception on the topic of Newton’s First Law in SMPN 3 Ketapang. This study was done in Pre-experimental method with one-group pre-test posttest design. The 29 sample were randomly chosen through intact group technique to the Class IX E students. The data collecting technique were 12 multiple choices questions for the pretest and postest to see the students’ misconception changes. From the analysis, the average percentage of students’ misconception before remediation given by using TGT Learning Model was 39,08%, while the average percentage of students’ misconception on the topic of Newton’s First Law after remediation given by using TGT Learning Model was 9,48%. The calculation of McNemar statistic test and Binomial test show that there is significant conceptual change of 5,93 point in each question answered by the students before and after the remediation. Based on the average value of proportion, ΔS = 0,75 was obtained with high effectiveness level. Therefore, remediating the students’ misconception by using TGT model on the topic of Newton’s First Law is effective in SMPN 3 Ketapang. Hopefully this result can be an alternative for the teacher in remediating students’ misconception on the topic of Newton’s First Law. Keywords: Misconception, TGT, Newton’s First Law